Aprendizaje de dibujo técnico de los alumnos de primer año - Bonafe, Silvana Noemi (2018)
Beginning with the research work: "The incidence of the instrumentation in the different Representation Systems in the training of industrial Designers", it is proposed to analyze the first exercises carried out by the students in the subject of the second year of the career of Industrial Design of the FAUD of the UNC “Systems of Representation II”.